Enhancing Sustainable Practices for Pesticide Management and Packaging Disposal in Rice Cultivation: A Case Study of Bac Tan Uyen District, Binh Duong Province, Vietnam - Nguyen Vu Duc Thinh; Ly Hoang Han (Journal of Global Innovations in Agricultural Sciences)
Vietnam's agricultural reliance, particularly on rice cultivation, raises concerns about pesticide usage and its packaging disposal, vital for sustainable and safe practices. This study focused on Bac Tan Uyen District in Binh Duong Province, Vietnam, assessing current practices, challenges, and opportunities for improvement in pesticide management. Through interviews with 100 rice farming households and rigorous data analysis, the study reveals the extensive use of 44 pesticides and 39 active ingredients (AIs) in the district. Notably, practices varied concerning pesticide choice, application, post-spraying actions, protective gear usage, and handling of pesticide packaging. The study highlights alarming trends like the utilization of hazardous AIs and improper disposal methods like burning or leaving empty pesticide containers in fields. However, positive aspects, such as high adherence to designated bins for empty containers (93%), were identified. The results emphasize the urgency of enhancing awareness and implementing sustainable practices for safe pesticide use and packaging disposal, crucial for environmental preservation and human health in rice cultivation. Keywords: Pesticide use, pesticide packaging, rice cultivation, Binh Duong, Vietnam.